Memotret Penilaian Kontekstual Pembelajaran Peserta Didik dalam Perspektif Pendidikan Umum/Karakter - Suharyanto H. Soro (Lembaga Pendidikan Islam Ma'aarif NU Kabupaten Magetan, 2024)
Contextual assessment has not been implemented and popularized in educational units. This needs to be studied or researched with the hope that the findings can be actualized both in the world of education and non-education. This study aims to find and analyze the application of contextual assessment in the teaching and learning process both in the classroom and outside the classroom carried out by educators to students in academic settings. The researcher used a case study approach. This approach is one of the qualitative research paradigms. The data collection method uses observation and interview methods. The results of the study indicate that contextual assessment is carried out through two approaches, namely the micro-scale and macro-scale approaches. Micro contextual assessment is oriented towards internal activities, both cognitive, affective, and psychomotor domains with different weights for each component so that it can be used as a valid measuring tool to state high, medium, and low values, or very good, good, sufficient, and less good. Macro contextual assessment is oriented towards activities that are carried out consciously by involving other components as part of the weight that is recognized as valid and supportive, and can be accounted for academically. So contextual assessment is an inseparable part in realizing a progressive human life and as proof that humans as creatures of Allah SWT are able to assess and differentiate by using cognitive, affective, and psychomotor domains according to their degree and existence as objects of assessment.